Functional Analysis of Oral-digital Stereotypy in a Student with Profound Mental Retardation (Malaysian Journal of Learning and Instruction, 2005)
The current study included two experiments that functionally analyzed stereotypical oral-digital behavior of one female student with profound mental retardation. An analogue functional analysis was used in Experiment 1 to detect the function of the student's oral-digital stereotypy which might serve to escape from task demands, obtain attention from others, or produce sensory self-stimulation. An analysis of sensory modalities was conducted in Experiment 2 to further analyze the possible sensory consequences maintaining the student's repetitive oral-digital. Results of the present study demonstrated that multiple consequences which included drawing attention from teachers and producing sensory stimulation could serve to maintain this student's stereotypy. The specific sensory function of this student's oral-digital stereotypy might be maintained by tactile stimulation. These findings were further discussed in terms of the sensory and social reinforcers that execute their impacts on this student's stereotypical behavior, and procedures used to detect those functions.